2013
DOI: 10.1111/cod.12157
|View full text |Cite
|
Sign up to set email alerts
|

Periorbital dermatitis in 4779 patients – patch test results during a 10‐year period

Abstract: Allergic contact dermatitis is a leading cause of periorbital dermatitis. Patch testing should be considered in all patients with periorbital dermatitis when contact allergy is suspected, in order to identify and avoid offending allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 29 publications
(48 reference statements)
6
48
3
2
Order By: Relevance
“…The high proportion of women in our study (90%) is similar to the percentage (70‐90%) reported in previous studies in other countries . It is higher than the 70% proportion of females in French patients patch tested for eczema with various localizations .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The high proportion of women in our study (90%) is similar to the percentage (70‐90%) reported in previous studies in other countries . It is higher than the 70% proportion of females in French patients patch tested for eczema with various localizations .…”
Section: Discussionsupporting
confidence: 88%
“…Overall, in 57 (67.9%) of the 84 patients with currently relevant positive test reactions, the dermatitis was attributable to cosmetics. In 11 patients, an eyelid treatment was responsible for the eyelid dermatitis: 8 eye drops, and 3 creams containing budesonide or neomycin . In 3 patients (all men), the eyelid dermatitis was attributable to an occupational allergen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1 large analysis, only 0.6% of >200 000 allergic contact dermatitis cases were caused by an airborne allergen, 35% of which were attributable to occupational exposure . Among almost 5000 periorbital dermatitis cases, only 2.6% were caused by an airborne allergen, and 3.6% were attributable to occupational exposure . One previous report described a case of eyelid allergic contact dermatitis caused by Disperse Blue 106, although ∼5% of patients with eyelid dermatitis react to Disperse Blue 106, one of the most common dye contact allergens tested, in patch testing .…”
Section: Discussionmentioning
confidence: 47%